2014
DOI: 10.1080/13676261.2014.881986
|View full text |Cite
|
Sign up to set email alerts
|

When bad food happens to good intentions: female students' food dilemmas

Abstract: Female students' food dilemmas are explored with a special focus on reasons why unhealthy food consumption happens in spite of the students' good intentions to eat healthy diets. The study takes a qualitative approach based on 11 in-depth interviews and 5 focus groups with Danish and international female students. Theoretically, the article draws on existing literature on food and student food consumption and on Warde's food consumption antinomies. The female students in this study find that they are well-info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…There are no significant differences among men and women on the health and value conscious self-image. While previous research (Glanz et al, 1998;Gram & Blichfeldt, 2014) showed that women were more health conscious than men, this study reveals that men are becoming more weight, brand, and variety conscious in their selection of healthy labeled foods. This change could probably be explained with changing sociodemographic environment where more and more men are choosing to remain single, or engaged in building a body or are staying at home to take care of kids and, in this process, improve the quality of diet consumed by them.…”
Section: Relationship Between Self-image Factors and Gendercontrasting
confidence: 77%
See 3 more Smart Citations
“…There are no significant differences among men and women on the health and value conscious self-image. While previous research (Glanz et al, 1998;Gram & Blichfeldt, 2014) showed that women were more health conscious than men, this study reveals that men are becoming more weight, brand, and variety conscious in their selection of healthy labeled foods. This change could probably be explained with changing sociodemographic environment where more and more men are choosing to remain single, or engaged in building a body or are staying at home to take care of kids and, in this process, improve the quality of diet consumed by them.…”
Section: Relationship Between Self-image Factors and Gendercontrasting
confidence: 77%
“…They may also be more brand loyal than men because the relationship with the variety conscious self-image was not significant. The results are supported by the study conducted by Gram and Blichfeldt (2014), which found that despite the fact that female students were more health conscious, their actual consumption of food was becoming more unhealthy due to lack of time and energy and work pressure.…”
Section: Relationship Between Self-image Factors and Gendermentioning
confidence: 52%
See 2 more Smart Citations
“…As a possible consequence of this lack of consistency between intentions and actual behavior, close to half of the female participants and a quarter of the male participants stated that they had a bad conscience when eating fast food. Correspondingly, in a study among young female students, the authors found a strong request in favor of consumption of healthy food; yet, their actual consumption of both healthy and unhealthy food causes them to experience dilemmas regarding their food consumption (Gram & Blichfeldt, 2014). Table 2 Participants' responses in relation to the level of agreement or disagreement to a series of statements and future wants for fast food according to gender.…”
Section: Inconsistency Between Purchase Intentions and Actual Behaviormentioning
confidence: 94%